Implementation of Material Control in Tugboat Ship Building Using the Lot For Lot (LFL) Method Case Study : (PT.PMP) - Baroroh, Intan Intan; Tarigan, Eko Febrianto; Sumantri, Siswo Hadi; Azhar, Ali; Hardianto, Dididk; Kristiyono, Tri Agung (International Journal of Marine Engineering Innovation and Research, 2024)
Material procurement in the shipping industry accounts for 2/3 of the total production cost.  PT.PMP is a company that focuses on the shipbuilding industry including Ship Design, Ship Building and Ship Repair. In the implementation of material procurement, there are often delays in the delivery of materials from suppliers resulting in delayed production time. Material inventory in the warehouse is sometimes insufficient to meet production needs. In the Pre-Order system, the company must ensure the availability of prepared planning items, but the Company sometimes faces a shortage of raw materials which results in delays in the delivery of promised goods. Material Requirement Planning (MRP) is a method used to organize and plan material orders. The purpose of this study is to determine the material planning strategy using the Lot for Lot method and the Economic Order Quantity method comparison between efficient methods at PT.PMP and to determine the efficiency results of the comparison between the Lot for Lot (LFL) method, Economic Order Quantity (EOQ) and the existing method at PT.PMP. The materials analyzed are Plate and Profile in the New Building Tugboat Project. The results obtained from the inventory cost research that the Lot for Lot method is 28%, the Economic Order Quantity method results in an inventory cost of 29% and the company method that is still being applied results in a high cost of 43%. The Lot for Lot method is more efficient by 15% than the existing method applied by the company.